Pengembangan Kurikulum Literasi Hukum Digital Untuk Pencegahan Kejahatan Siber Pada Remaja - Moh. Wahyu Romadlon; Reza Fauzi Nazar; Moh. Saddad Muhibbi; M. Abdul Rohman; Triana Galuh Purnama Sari; Sonia Isna Suratin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has had a significant impact on adolescent behavior and interaction patterns, including increasing the risk of involvement in cybercrime. This situation demands strengthening digital legal literacy through the development of a curriculum that is relevant, systematic, and responsive to the challenges of the digital era. This study aims to analyze the needs, challenges, and opportunities in designing an effective digital legal literacy curriculum to prevent cybercrime among adolescents. The research method used was a literature review with a qualitative approach, examining various academic sources, regulations, journals, and reports related to digital literacy, legal education, and cybersecurity issues. The results indicate that adolescents' lack of understanding of digital ethics, legal regulations, and the consequences of online actions are factors that increase the potential for cyber violations. On the other hand, the digital era provides significant opportunities through the use of interactive media, adaptive learning modules, and educational platforms that can strengthen legal awareness. The novelty of this study lies in the formulation of a strategic framework for developing a digital legal literacy curriculum that includes improving educator competency, integrating cyber law material into the school curriculum, and utilizing technology as a preventive educational tool. Thus, the development of a digital legal literacy curriculum is expected to be a strategic step in shaping responsible digital behavior while preventing cybercrime among adolescents.